Eficacia del helmet C-PAP como manejo inicial de tratamiento ventilatorio en pacientes con COVID-19 críticos, Lima 2021 - Visalot Gonzales, Giannina (2022)
OBJECTIVE: To determine the efficacy of non-invasive ventilation using the CPAP helmet system to reduce the need for mechanical ventilation in patients with ARDS due to SARS-CoV-2 treated at the Hipólito Unanue National Hospital from October to December 2021. MATERIAL AND METHODS: A quantitative, observational, non-experimental, retrospective, analytical study of a control group, cohort design, was carried out. Study to determine the effectiveness of the Helmet C-PAP as the initial management of ventilatory treatment in critically ill patients with COVID 19, during the year 2021. For the analysis, the information collected will be tabulated and the results will be interpreted through the statistical program SPSS v24. RESULTS: They will be obtained according to the completion of the schedule for data analysis. CONCLUSIONS: They will be carried out once the results are obtained.